2016
DOI: 10.3171/2015.6.spine15140
|View full text |Cite|
|
Sign up to set email alerts
|

Screening via CT angiogram after traumatic cervical spine fractures: narrowing imaging to improve cost effectiveness. Experience of a Level I trauma center

Abstract: OBJECT Screening for vertebral artery injury (VAI) following cervical spine fractures is routinely performed across trauma centers in North America. From 2002 to 2007, the total number of neck CT angiography (CTA) studies performed in the Medicare population after trauma increased from 9796 to 115,021. In the era of cost-effective medical care, the authors aimed to evaluate the utility of CTA screening in detecting VAI and reduce chances of posterior circulation stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…A conventional angiography, a CT angiography (CTA), or magnetic resonance imaging (MRI) angiography are potential tools used to detect a vascular lesion or an anatomical anomaly (eg, high riding artery). 10 - 12 …”
Section: Diagnosismentioning
confidence: 99%
“…A conventional angiography, a CT angiography (CTA), or magnetic resonance imaging (MRI) angiography are potential tools used to detect a vascular lesion or an anatomical anomaly (eg, high riding artery). 10 - 12 …”
Section: Diagnosismentioning
confidence: 99%
“…They found CTAs ordered off protocol had a very low likelihood of having a VAI, the incidence of CTA changing the surgical intervention of the patient was likewise low (1 of 126, 0.8%), and C1-C3 spine injuries have an increased association with VAI. Similarly, in a retrospective study ranging 10 years and encompassing 732 patients, Lockwood et al 20 found that C1 and C2 fractures along with those involving the foramen transversarium and subluxation injuries, were associated with an increased risk of VAI. Additionally, they found that only 7.8% (4 of 51) of these VAIs and 0.6% (10 of 732) of all CTAs conducted, ended up with a posterior stroke.…”
Section: Discussionmentioning
confidence: 93%
“…However, given the cost and inherent procedural risks, screening DSA has largely been replaced by CTA or MR angiography 16. CTA has been found to be between 97.7% and 100% sensitive in screening for blunt traumatic cerebrovascular injury in both retrospective17 and prospective series 18.…”
Section: Discussionmentioning
confidence: 99%